Wearing Many Hats: Supply Managers Behavioral Complexity and Its Imapct on Supplier Relations - Wu,Zhaohui; Steward,M.; Hartley,J. (Journal of Business Research, 2009)
Applying concepts from the behavioral complexity literature (Ashby, 1952; Denison, Hooijberg, and Quinn, 1995) we examine if supply managers’ multiple roles and the ability to shift among these roles is related to their interpersonal relationship with their key contact within the strategic suppliers’ organization and ultimately with the firm-to-firm relationship. Case studies identified four supply manager roles that are assumed when managing relationships with strategic suppliers: negotiator, facilitator, supplier’s advocate, and educator. Survey data were gathered from 59 pairs of supply managers and their key contact in a strategic supplier’s organization. Results show that a larger behavioral repertoire is positively related to interpersonal relationships but higher behavioral differentiation is negatively related to interpersonal relationships. Interpersonal relationships are positively related to firm-to-firm relationships. Limitations and opportunities for future research are discussed.
Keywords: Supply Chain